2009
DOI: 10.1016/j.rmed.2009.04.021
|View full text |Cite
|
Sign up to set email alerts
|

A predictive model of hospitalisation and death from chronic obstructive pulmonary disease

Abstract: We have developed a model that estimates the risk of respiratory hospitalisation and death in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 16 publications
(7 reference statements)
4
45
0
2
Order By: Relevance
“…All models included a strong association between age and mortality, which was in line with studies found in the literature [32,33,[35][36][37][38]. Validation against trial results also showed a difference in 12 mortality between young and old patients for the trial as well as most models.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…All models included a strong association between age and mortality, which was in line with studies found in the literature [32,33,[35][36][37][38]. Validation against trial results also showed a difference in 12 mortality between young and old patients for the trial as well as most models.…”
Section: Discussionsupporting
confidence: 85%
“…The difference in mortality is less clear from the literature. Some studies reported lower mortality rates for females [32][33][34], while others found no difference [35][36][37][38]. Only two models specified quality of life by gender, while several studies found a lower quality of life for female patients [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…We also calculated modifications of the BODE index, including the mBODE (which replaces 6MWD with oxygen uptake) [20], e-BODE (BODE plus exacerbations) [21], and BODEx (substitution of exacerbations for exercise capacity) [21]. We also calculated the ADO index (age, dyspnoea and FEV1) [22], the COPD Prognostic Index (CPI) (quality of life standardised by the Chronic Respiratory Questionnaire (CRQ) or St George's Respiratory Questionnaire (SGRQ), FEV1, age, sex, BMI, exacerbation history and cardiovascular disease history) [23], the SAFE index (quality of life by SGRQ, FEV1 and 6MWD) [24], the HADO index (health status, activity, dyspnoea and FEV1) [25], the COPDSS-COPD severity score (respiratory symptoms, systemic corticosteroid use, other COPD medication use, previous hospitalisation or intubation for respiratory disease and home oxygen use) [26,27], TARDIS (age, BMI, dyspnoea, airflow obstruction, hospitalisations and influenza vaccination) [28], and the DOSE index (dyspnoea, smoking status, FEV1 and prior exacerbation history) [29]. Comorbidities were quantified by means of the Charlson index, excluding COPD [30].…”
Section: Indices Calculationsmentioning
confidence: 99%
“…The strength of our disease-specific database lies within all patients having a diagnosis of COPD made by a primary or secondary care physician, thereby providing us with an unselected community population of COPD patients for analysis [14]. We acknowledge that our study has limitations given that it was retrospective and observational in design.…”
Section: Discussionmentioning
confidence: 99%
“…TARDIS is a COPD disease-specific database that has previously been used as the basis for previous published COPD research, thereby providing us with an unselected community population of COPD patients for analysis [14,15].…”
Section: Methodsmentioning
confidence: 99%